(untitled) (Journal of Management and Social Sciences, 2026)
It is impossible to overstate the value of workers in the manufacturing sector as they influence the sector’s success and, in turn, the economy of the country. This study examined how employees’ schemes to leave Nigerian manufacturing industries were influenced by talent management strategies, including human resource planning, recruitment and selection, employee development, employee retention, employee health and safety management, and employee performance appraisal. A descriptive survey research design was used in the study. The study’s target population was 3,172 employees from the six Nigerian manufacturing industries. Only 952 respondents were chosen for the study using basic random sampling methods and stratified sampling. The validity and reliability of two study tools—the Employees’ Turnover Schemes Questionnaire and the Talent Management Strategies Questionnaire—were determined. A research question was posed, and inferential statistics were used to assess the hypothesis. The results show that workers have low schemes to leave, that all of the talent management techniques under consideration are widely used, and that the total and relative contributions of these strategies to employees’ schemes to leave are much higher. According to the recommendations, organisations should implement more talent management strategies, assess the efficacy of their talent management practices regularly, and enhance their retention initiatives in light of the talent management strategies that have been found to have a major impact on employees’ schemes to leave. Keywords Talent Management Strategies and Employee Turnover Schemes